Overcoming Forgetting and Boredom in Learning - Muhammad Ali; Muhibbin Syah; Samsul Arifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The purpose of this research is to examine matters related to forgetting, saturation and transfer in learning. The research method used is a qualitative method with the type of research being library research. Furthermore, forgetting and getting bored with learning are things that every student will experience. Forgetting and boredom are negative events, these things happen because of various factors that cause these things to happen. With these factors in place, tips or solutions emerge to overcome or at least reduce these incidents.